Carvacrol incorporation into novel controlled-release mucoadhesive systems for oral polymicrobial biofilm control - Sales, Luciana Solera [UNESP] (2024)
The aim of this study was to evaluate carvacrol antimicrobial activity in polymicrobial biofilms using a novel controlled-release mucoadhesive systems developed from biopolymers. The natural polymers gellan gum and sodium alginate were used in different concentrations for the development of films, tablets and microparticles containing carvacrol. The systems were characterized as regard their morphological characteristics, carvacrol release and mucoadhesion. Furthermore, the antimicrobial activity of the systems was evaluated on polymicrobial biofilms through biomass quantification and microbial viability assessment. Carvacrol release profile from films, tablets and microparticles was similar; nearly 100% of the carvacrol was released within 15 min. Films showed the best mucoadhesion values. Scanning Electron Microscopy images showed that the films presented a continuous and smooth surface, and the tablets showed a continuous surface with a polymer web appearance. The microparticles were spherical in shape. The films containing carvacrol showed the highest biomass and microbial viability reduction, followed by the tablets. The findings of this study showed that carvacrol incorporated into films and tablets presented antimicrobial activity on polymicrobial biofilm. Controlled-release mucoadhesive systems is a process little explored in dentistry, being the differential of this work, and with great innovative potential for the management of dental diseases.